USM 53rd CONVOCATION 30th APRIL 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 25 February 2016 Universiti Sains Malaysia (USM) will be having the 53 Convocation Ceremony on Saturday, 30th April 2016.